Incorporation of fish protein gel from shark meat into fishery products - Bisheswar Prasad (Department of Processing Technology, College of Fisheries, 2004)
A study was undertaken for the incorporation of fish protein gel from shark meat into fishery products. Fish sausage was prepared with and without protein gel. Standardization was done based on various combinations of starch, protein gel and ice water and most acceptable combination was selected. Fish meat was mixed with various food additives such as salt, sugar, starch or fish protein gel, monosodium glutamate, colour and water and stuffed into cellulose casings, cooked, cooled, packed using low-density polyethylene of thickness 300 gauge, subjected to freezing and stored at –200C in frozen condition. The various starch: protein gel: ice water proportion used for study were 10: 0: 10, 10: 5: 5, 10: 10: 0 and 5: 15: 0. The effect of protein gel was assessed based on gel strength and sensory evaluation of products. Based on these parameters, the following proportion 10: 10: 0 of starch: protein gel: ice water was selected. Fish sausages were prepared using the standardized method and subjected to storage studies along with a control in frozen condition at temperature of freezing -200C. Quality changes during storage were monitored at appropriate time interval based on various tests, viz., moisture content, peroxide value, total volatile base nitrogen content, pH, gel strength, sensory evaluation, total plate count and fungal count. Both control and test were acceptable with no significant reduction in sensory quality during frozen storage. Products were acceptable throughout storage period. Both products showed some changes in moisture content, pH, gel strength and TVBN content with storage period. Products were remained acceptable up to 60 days of storage. The Gel incorporated product appeared to be slightly the better of the two based on sensory responses eventhough statistically there was no significant difference.